Variations in storm-induced bed level dynamics across intertidal flats - P. L. M. de Vet (Nature Portfolio, 2020)
Abstract Hydrodynamic forces on intertidal flats vary over a range of temporal and spatial scales. These spatiotemporal inhomogeneities have implications for intertidal flat morphodynamics and ecology. We determine whether storm events are capable of altering the long-term morphological evolution of intertidal flats, and unravel the contributions of tidal flow, wind-driven flow, waves, and water depth on inhomogeneities in bed level dynamics (bed level changes over ~days) across these areas. We complement decades of bed level measurements on eight intertidal flats in two estuaries in the Netherlands with an extensive 1-month field campaign on one of those flats. Across this intertidal flat, the hydrodynamics and morphodynamics of a storm event were captured, including the post-storm recovery. We show that individual events can persistently alter the morphological evolution of intertidal flats; magnitudes of some bed level changes are even comparable to years of continuous evolution. The morphological impacts of events are largely controlled by the relative timing of the forcing processes, and not solely by their magnitudes. Spatiotemporal variations in bed level dynamics of intertidal flats are driven by a combination of: (1) the inhomogeneous distributions of the hydrodynamic forcing processes (including the under-explored role of the wind); and (2) the linear proportionality between bed level dynamics and the local bed slope.